Women’s behavior of consuming digital technologies - Lins, Samuel Lincoln Bezerra; Weiler, Karina de Lemos; Pereira, Rita de Cássia de Faria; Beck, Ceres Grehs (Revista de Administração da UFSM, 2018)
The relationship between consumption behavior and gender has been a common interest in marketing studies. Whether from a biological perspective or from the perspective of gender identity, there is a correlation between the consumption of products or services and the fact that the consumer is a woman or a man. We investigated the consumption behavior of digital technologies by women through an exploratory study with in-depth interviews with 15 working women aged between 22 and 30 years. Content analysis revealed three profiles of female consumers: engaged, interested, and disinterested. Besides, mass media was revealed as an important source of influence on the purchasing process, and the Internet was identified as the main information source about the items to be purchased. Our research also shows that the interest about and the consumption of digital technologies by women are increasing. However, women are still in need of additional technical knowledge and the opinion of other people to feel more secure about purchasing technology. The findings address the relevance of studying the relationship between technology consumption and gender from the perspective of the consumer, the decision maker or the agent that exerts influence on the purchasing process.